Translation of Cultural References in the English Subtitles of Nussa Short Movie Special Edition: ‘Kamu… Antta’ - Safi'i, Muhamad; Panggabean, Hanna Maria; Losi, Rizky Vita; Harahap, Ahmad Fadli; Siregar, Try Mahendra (IAIN KENDARI, 2026)
This study aims to identify and analyze the translation strategies used in translating culture-specific items (CSIs) from Indonesian into English subtitles in the Nussa short movie special edition titled